PLA-HA/Fe3O4 magnetic nanoparticles loaded with curcumin: physicochemical characterization and toxicity evaluation in HCT116 colorectal cancer cells - Bourang, Shima; Asadian, Sina; Noruzpour, Mehran; Mansuryar, Atefeh; Azizi, Solmaz; Ebrahimi, Hossein Ali; Amani Hooshyar, Vahid (Discover applied sciences, 2024)
Colorectal cancer (CRC) is the third most common, harmful, and universal cancer and the second lethal type. This paper discusses the therapeutic potential of curcumin, a significant curcuminoid found in the substructure of plant Curcuma longa (turmeric), against CRC. Curcumin has the ability to disrupt a variety of cellular signaling pathways and has been validated in several preclinical and clinical studies, but suffers from low solubility and bioavailability. Despite the widespread use of curcumin (CU) against colorectal cancer, it presents limitations, such as low solubility and bioavailability. Due to these drawbacks, researchers focused on new methods to carry CU into cells to overcome the limits of treatments with CU. One of the leading solutions is bioanalytical methods, which are based on using CU in combination with nanoparticles, especially magnetic nanoparticles, which cause the targeted transfer of the drug to cancer cells. To address these issues, PLA-HA/Fe 3 O 4 magnetic nanoparticles were synthesized and loaded with curcumin. The average size and zeta potential of the nanoparticles and the magnetic properties were measured. The drug encapsulation efficiency and cumulative release of curcumin from the nanoparticles under acidic and neutral pH (4.8, 6, and 7.4) values were evaluated, as well as the cytotoxic effect of the nanoparticles on HCT116 colorectal cancer cells. According to the results of DLS and TEM analysis, PLA/Fe 3 O 4 /curcumin nanoparticles had a spherical structure with an average size of 208 Å ± 12.8 nm and a Zeta potential of − 18 (mV). The drug encapsulation efficiency in PLA-HA/Fe 3 O 4 nanoparticles was 24.8 ± 4.6 percent. The drug's release rate was influenced by acidic and neutral pH levels. After 14 days, the highest release rate was 98% at pH 4.8 and over 94% at pH 6 (typical of cancer cells). In contrast, the drug's release at pH 7.4 (typical of healthy cells) after 14 days was only 59%. The results demonstrated that nanoparticles have a high degree of biocompatibility and the ability to carry Curcumin medications. HCT116 cells with 200 μg/ml PLA-HA/Fe 3 O 4 /Curcumin nanoparticles have 58.63 ± 3.7% percent cell viability. Ultimately, PLA-HA, Fe 3 O 4 , and Curcumin's physicochemical characteristics and impact on cell viability render them valuable instruments for precisely delivering drugs to colorectal cancer cells. The PLA-HA/Fe 3 O 4 –curcumin nanoparticles demonstrated a well-targeted drug delivery system for upcoming colorectal cancer treatments, as evidenced by their strong cytotoxic effects on colorectal cancer cells and negligible toxicity towards non-cancerous cells. Graphical abstract Study Highlights Silybum marianum seed methanolic extract was used as a reducing agent to synthesize NPs. Innovative PLA-HA/Fe 3 O 4 –curcumin nanoparticles show promising potential as a targeted drug delivery system for colorectal cancer treatment. These nanoparticles exhibit high drug encapsulation efficiency, controlled release at acidic pH levels typical of cancer cells, and significant cytotoxic effects on colorectal cancer cells while maintaining biocompatibility and minimal toxicity towards healthy cells. This novel approach addresses the limitations of curcumin therapy and offers a valuable tool for precise drug delivery in colorectal cancer treatment.